PENTINGNYA SARANA IBADAH SEBAGAI PENUNJANG PENDIDIKAN AGAMA ISLAM DI SDN 004 SAMARINDA UTARA - Qomariah, Annisa; Afdal; Al Qamariah, Fuzi (SISTEMA: Jurnal Pendidikan, 2021)
This study aims to determine the means of worship as a support for Islamic religious education at SDN 004 North Samarinda. The type of research is descriptive qualitative research. The research subjects used a purposive sampling technique, namely the principal, Islamic Religious Education teacher and five fifth grade students. Data collection techniques through interviews and documentation. Data analysis techniques with data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the worship facilities at SDN 004 North Samarinda still use classrooms. The facilities of worship still have many shortcomings, but they can still be used for worship and teaching and learning in Islamic Religious Education subjects such as practice in schools. Keywords: Facilities of Worship, Islamic Religious Education, Elementary School